HLA micropolymorphisms confine neoantigen conformational adaptability and guide T cell receptor selectivity - Jiaqi Ma; Cory M. Ayres; Chad A. Brambley; Bassant Eldaly; W. W. J. Gihan Perera; James A. Lazar; Evgenii L. Kovrigin; Smita S. Chandran; Christopher A. Klebanoff; Brian M. Baker (Proceedings of the National Academy of Sciences, 2026)
T cell receptor (TCR) restriction by highly polymorphic major histocompatibility complex (MHC) proteins is a foundation of cellular immunity. Although the effects of MHC polymorphisms on peptide binding and selection are well established, how micropolymorphisms within MHC supertypes impact immune recognition is poorly understood. Here, we identified a mechanism through which the micropolymorphisms in two closely related HLA-A3 superfamily members govern TCR specificity. We previously showed that TCRs specific for a public neoantigen arising from a PIK3CA oncogenic hotspot mutation restricted by HLA-A*03:01 were unable to recognize the same epitope in the context of HLA-A*03:02 despite equivalent processing and presentation by both alleles. We found here that the two micropolymorphisms distinguishing A*03:02 from A*03:01 prevent TCR binding not by altering peptide binding or static structures, but by altering the conformational ensemble of the neoantigen, preventing it from adopting a binding-permissive state. The effect is rooted in how the two polymorphic sites interact with other covarying, evolutionarily coupled polymorphisms, reflecting a cross-groove network of interactions that controls the conformational adaptability of the peptide/HLA complex. We suggest polymorphism-dependent adaptability reflects an evolved feature of class I MHC proteins, further diversifying epitopes and contributing to how TCRs and other immunoreceptors differentiate between antigens. Beyond this mechanistic insight, our findings emphasize the need for high-resolution HLA typing in efforts across immunology, including antigen-specific immunotherapy.